Analysis of somatic mutations in kappa transgenes (The Rockefeller University Press, 1990)
We have examined the nature and localization of somatic mutations in three kappa transgenes cloned from IgG-secreting hybridomas. All of the mutations identified were single base substitutions. Mutations were localized to the variable (V) region and its flanking sequences. In every case, the nuclear matrix association region, kappa enhancer, and C gene were spared. These data indicate that the rearranged kappa gene contains the necessary sequences for targeting of the mutation process, and suggest that the observed localization of mutations to the V region reflects the inherent specificity of this mutation process.